IMPLEMENTASI PROGRAM CINTA (CICING TENANG TANPA RUNTAH) BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) DALAM MENINGKATKAN KOMPETENSI KEBERLANJUTAN MURID SEKOLAH DASAR - Pancarini, Kus; Nurul Maulida, Vita; Mahpudin, Pupud; Mirnawati, Mira; Jaenudin, Dadang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low environmental awareness and the suboptimal implementation of Education for Sustainable Development (ESD) in primary schools pose challenges to fostering students'